Protective effect of polydatin, a natural precursor of resveratrol, against cisplatin-induced toxicity in rats - Ince, Sinan; Arslan Acaroz, Damla; Neuwirth, Ondřej; Demirel, Hasan Huseyin; Denk, Baris; Kucukkurt, Ismail; Turkmen, Ruhi (Food and chemical toxicology, 2014)
The aim of the present study was to evaluate the possible protective effect of polydatin (PD) on cisplatin (Cis) induced oxidative stress in rats. Totally, thirty male Wistar albino rats were fed standard rodent diet and divided into 5 equal groups: the control group (vehicle treated) was treated with physiological saline for ten days both orally and intraperitoneally (i.p.), the second group was orally treated with physiological saline and 7 mg/kg single i.p. injection of Cis on the seventh day, and third, fourth, and fifth groups were treated orally PD at 25, 50, and 100 mg/kg/day, respectively for 10 days starting seven days before Cis injection and 7 mg/kg single i.p. Cis was injected on the seventh day. Cis resulted in significant increase malondialdehyde levels and decreased glutathione levels. In addition, Cis treatment decreased superoxide dismutase and catalase activities in erythrocyte and tissues. Also, Cis treatment caused to increase DNA damage and affected serum biochemical parameters whereas slightly decreased AchE activity. However, treatment of PD resulted in reversal of Cis-induced oxidative stress, lipid peroxidation, and activities of antioxidant enzymes. In conclusion, PD has protective effect in rats against Cis-induced oxidative stress, enhances antioxidant defence mechanism, and regenerates their tissues.
Keywords: Animals; katalasa; DNA Damage; Superoxide Dismutase; cisplatina; Antioxidants; Glucosides; glutathion; oxidační stres; Catalase; Rats, Wistar; Glutathione; Cisplatin; superoxiddismutasa; glukosidy; Resveratrol; erytrocyty; Oxidative Stress; stilbeny; Stilbenes; DNA damage; peroxidace lipidů; resveratrol; Lipid Peroxidation; Oxidative stress; poškození DNA; Male; Erythrocytes; Malondialdehyde; Rat; antioxidancia; krysa rodu Rattus; malondialdehyd; zvířata; mužské pohlaví; Rats; Polydatin; Toxicity; potkani Wistar